Manufacture of compression moulded PLA based biocomposites: A parametric study. (1st November 2015) - Rubio-López, A.; Olmedo, A.; Díaz-Álvarez, A.; Santiuste, C.
Abstract: In this study, an analysis of the fabrication parameters that influence on the strength of biodegradable composites is presented. The effect of heating temperature, pressure, number of plies, fibre, and matrix on the tensile strength was studied. Biodegradable composites were manufactured using film stacking and compression moulding process. The strengths of biocomposite based on two different polylactic acid (PLA) matrix, and reinforced with four different woven fibres of jute, flax and cotton were compared. The aim of this work is the development of an optimised manufacture process to reduce costs and production time of high strength biocomposites. As a result, a tensile strength higher than 100 MPa was obtained with a preheating time of 2 min and 3 min of heating under pressure. This result means a significant reduction of production time that can lead to reduce the manufacture cost of these materials.